THE CRIME OF OMISSION TO FAMILY ASSISTANCE FROM CLINICAL CRIMINOLOGY - Alberto Javier Coarite Andrade (2020)
The omission of family assistance, within Creole slang, is related to a debt criminology, the absence of payment of food to children. But the sphere that it protects is greater, greater than a monetary aspect, is a fundamental piece of constitutional recognition, of defense to the members of the family. The social context helps us to formulate that the omission for family assistance is caused by an incidence at an early age, in addition to this, the context in which it develops, that is, the geographical space is also a determining factor; However, knowledge of the field is not enough, which is why we must add the biological factor. Therefore, a knowledge and study of the agent, from the perspective of clinical criminology, can help to understand the reasons which can lead to committing this antisocial behavior. Now. Clinical criminology includes the study of the individual from three approaches: biological, psychological and social. From the biological field, information was collected from scientific articles that provide information on what are the biological, hormonal characteristics that direct the agents to perform such behavior and what is their influence on human behavior. From the above, no major approach has been made because I know if you want to be certain with statistical data, these should be done based on blood tests, but that we have been limited for reasons of money and time. In the psychological field, the study of a specific and real case was carried out. What is sought in this section is to explore whether parental-subsidiary relationships have an impact on adult life and the development of other types of relationships, also, if the degree of instruction affects this type of behavior, that is, if the agent Whether or not you are fully aware of the responsibility you incur when having a child. From the social approach, through consultation with psychologists and statistics, an approach of which are the social characters can be made, accompanied by it, the influence of the accelerated pace of life that is lived today. From all of the above, it will offer us a greater perspective of what exists behind the commission of the omission to family assistance and that the crime, despite being typified in our penal code, harbors aspects that the law fails to focus on, a more humanitarian side.